Merkel cell carcinoma induces lymphatic microvessel formation - Werchau, Siegfried Arthur; Toberer, Ferdinand; Enk, Alexander; Helmbold, Peter (Journal of the American Academy of Dermatology, 2012)
Background: Merkel cell carcinoma (MCC) is a rare, highly malignant neuroendocrine tumor of the skin characterized by frequent lymphatic metastasis. Objective: We sought to identify lymphovascular anatomy and expression profiles of lymphangiogenic cytokines to give an opinion on lymphangiogenesis in MCC. Methods: We studied lymphatic microanatomy and lymphangiogenic cytokines in 27 MCC by immunohistology or immunofluorescence (D2-40, lymphatic vessel endothelial hyaluronan receptor [LYVE-1], vascular endothelial growth factor [VEGF] receptor-3, VEGF-C, VEGF-D, Ki67/MiB-1, CD68/PG-M1, CD68/KP1, CD163), Merkel cell polyomavirus-specific polymerase chain reaction, and coanalysis with clinical and histologic data. Results: We found a more than 3-fold increase in the mean density of absolute numbers of small lymphatic capillaries (diameter <10 μm) and a more than 8-fold increase in the median ratio of the number of small to large lymphatics (<10/≥10 μm) paratumorally compared with intraindividual controls. VEGF-C+CD68+ CD163+ cells (interpreted as M2 macrophages) could be identified as an important potentially lymphangiogenesis-inducing cell type. Limitations: Partially lacking follow-up data limited the analysis of the prognostic impact. Conclusions: Our findings strongly indicate lymphangiogenesis in MCC driven by VEGF-C+CD68+ CD163+ M2 macrophages.
Published online: September 4, 2011
Gesehen am 26.11.2018